2004
DOI: 10.1128/iai.72.3.1594-1602.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antigen Identification Method for Discovery of Protective Malaria Antigens by Rapid Testing of DNA Vaccines Encoding Exons from the Parasite Genome

Abstract: We describe a novel approach for identifying target antigens for preerythrocytic malaria vaccines. Our strategy is to rapidly test hundreds of DNA vaccines encoding exons from the Plasmodium yoelii yoelii genomic sequence. In this antigen identification method, we measure reduction in parasite burden in the liver after sporozoite challenge in mice. Orthologs of protective P. y. yoelii genes can then be identified in the genomic databases of Plasmodium falciparum and Plasmodium vivax and investigated as candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Twenty of the protective sequences Ͼ50 aa in length encode previously untested hypothetical proteins, and 14 of these proteins showed conservation across several malaria species, suggesting that conserved hypothetical proteins may be contributing to the observed crossprotection. This is analogous to results of Melby et al (39), who identified pools of protective hypothetical proteins within a Leishmania ELI vaccine, and Haddad et al (24), who identified hypothetical proteins in a P. yoelii liver-stage exon DNA vaccine pool. Our next objective is to further segregate the sequences to identify the minimal number of plasmids capable of inducing cross-protection.…”
Section: Discussionsupporting
confidence: 60%
“…Twenty of the protective sequences Ͼ50 aa in length encode previously untested hypothetical proteins, and 14 of these proteins showed conservation across several malaria species, suggesting that conserved hypothetical proteins may be contributing to the observed crossprotection. This is analogous to results of Melby et al (39), who identified pools of protective hypothetical proteins within a Leishmania ELI vaccine, and Haddad et al (24), who identified hypothetical proteins in a P. yoelii liver-stage exon DNA vaccine pool. Our next objective is to further segregate the sequences to identify the minimal number of plasmids capable of inducing cross-protection.…”
Section: Discussionsupporting
confidence: 60%
“…With the completion of the Plasmodium falciparum Genome Project, bioinformatic approaches are now being used (17). Large numbers of sequences predicted as exons from Plasmodium genomic databases have been screened as DNA vaccine constructs (18).…”
mentioning
confidence: 99%
“…Thus, the entire forward and reverse primer sequences used here in the amplification of the Pbs48/45 gene were 5Ј-GCAGG CTCCACCATGAATGAGTATGTTTCTCCAGATGAA-3Ј and 5Ј-AGAAAG CTGGGTTTACATAAAACCAGTTATTTTATCCAT-3Ј, respectively. PCR amplification and Gateway cloning was carried out using conditions described previously (14). A fragment of approximately 1.2 kb was obtained by PCR amplification for 35 cycles consisting of 94°C for 30 s, 52°C for 60 s, and 68°C for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Entry and DV1020 clones were analyzed by PCR and sequencing using vector-specific primers (14). Plasmid DNA from a confirmed DV1020-Pbs48/45 clone was prepared and purified using an endotoxin-free plasmid purification Giga kit (QIAGEN Inc., Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation